Factor price equalisation in the UK? - Abdrew B. Bernard; Stephen Redding; Peter K. Schott; Helen Simpson (Institute for Fiscal Studies (IFS), 2002)
This paper develops a general test of factor price equalization that is robust to unobserved regional productivity differences, unobserved region-industry factor quality differences and variation in production technology across industries. We test relative factor price equalization across regions of the UK. Although the UK is small and densely-populated, we find evidence of statistically significant and economically important departures from relative factor price equalization. Our estimates suggest three distinct relative factor price areas with a clear spatial structure. We explore explanations for these findings, including multiple cones of diversification, region-industry technology differences, agglomeration and increasing returns to scale.
Keywords: F11; F14; C14; 330; Relative Factor Prices; Diversification Cones; Technology; Economic Geography; Faktorpreisausgleich; Produktivität; Regionale Disparität; Schätzung; Großbritannien